Autophagy is required for sea urchin oogenesis and early development. Issue 6 (December 2016) - Agnello, Maria; Chiarelli, Roberto; Martino, Chiara; Bosco, Liana; Roccheri, Maria Carmela
Summary: Autophagy is a major intracellular pathway for the degradation and recycling of cytosolic components. Emerging evidence has demonstrated its crucial role during the embryo development of invertebrates and vertebrates. We recently demonstrated a massive activation of autophagy in Paracentrotus lividus embryos under cadmium stress conditions, and the existence of a temporal relationship between induced autophagy and apoptosis. Although there have been numerous studies on the role of autophagy in the development of different organisms, information on the autophagic process during oogenesis or at the start of development in marine invertebrates is very limited. Here we report our recent data on the occurrence of autophagy at these key phases of development. In order to investigate autophagy trends we performed in vivo assays to detect autophagolysomes, as well as in situ analysis with anti-LC3 antibody to detect autophagosomes before the fusion with lysosomes. From data generated through confocal laser scanning microscopy and quantification of autophagic signals we have drawn several unequivocal conclusions. The results showed a copious and rising number of autophagic organelles that had specific localization. Interestingly the increase in autophagy that occurred just after fertilization has been proved to be crucial for correct initiation of the developmental programme: irreversible developmental delays and morphologic anomalies were induced by short autophagic inhibition. This work focused on the sea urchin model system and corroborates evidence on the need for self-digestion during development, enriching the knowledge on autophagy, a biological mechanism belonging to evolutionarily different organisms.